PENGARUH KUALITAS PELAYANAN SAMSAT DRIVE THRU TERHADAP KEPUASAN MASYARAKAT DI POLDA METRO JAYA - Jarot Prianggono; Heru Adrian (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
Quick Wins program that prioritizes transparency is a program to improve job performance by means of maximizing public services. One of the police service improvement program to the public is the process of issuance of Vehicle registration plates (vehicle registration). This is accomplished by holding Samsat Drive Through; the vehicle registration renewal management services by using information technology facilities. Generally, This study aims to measure public satisfaction regarding the services of Samsat Drive Thru given by Polda Metro Jaya (Jakarta Police Department). This study uses quantitative approach with survey methods. Results of the study proved a link between the quality Samsat Drive Thru service and satisfaction the user community at Polda Metro Jaya. Furthermore there is a strong enough influence between quality Samsat Drive Thru service and public satisfaction in the Polda Metro Jaya. While the factors that affect the quality of Samsat Drive Thru service to the public satisfaction at Polda Metro Jaya is community participation, awareness of law and public compliance with laws and legislation especially in the field of traffic is increasing.